2022
DOI: 10.1111/pedi.13290
|View full text |Cite
|
Sign up to set email alerts
|

The association between depression symptom endorsement and glycemic outcomes in adolescents with type 1 diabetes

Abstract: Objective The prevalence of depression among adolescents with type 1 diabetes is estimated to be 2–3 times higher than in the general population. In adults with type 1 diabetes and depression, short‐term outcomes are worse compared to individuals just diagnosed with type 1 diabetes. This study aims to determine if depressive symptom endorsement is associated with glycemic outcomes and short‐term complications in adolescents with type 1 diabetes. Research Design and Methods Analysis was conducted using electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…Only DPV and SWEET collect CGM raw data files providing information on daily and ambulatory glucose profiles though only for a subgroup of individuals. PROM and/or PREM are currently collected by DPV, NCDR, NPDA, and T1DX‐QI using surveys with questions on health‐related quality of life, psychological well‐being, and experience with diabetes care 25–27 …”
Section: Work Flow and Description Of Registriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Only DPV and SWEET collect CGM raw data files providing information on daily and ambulatory glucose profiles though only for a subgroup of individuals. PROM and/or PREM are currently collected by DPV, NCDR, NPDA, and T1DX‐QI using surveys with questions on health‐related quality of life, psychological well‐being, and experience with diabetes care 25–27 …”
Section: Work Flow and Description Of Registriesmentioning
confidence: 99%
“…using surveys with questions on health-related quality of life, psychological well-being, and experience with diabetes care. [25][26][27] Overall, data completeness within each registry in the pediatric population is high with regard to indicators of diabetes control, daily insulin dose, and documentation of treatment modality (Table 4). With…”
Section: Sweetmentioning
confidence: 99%
“…Type 1 DM patients require multiple daily insulin injections (≥ 4 under the basal-bolus regimen), frequent checking of blood glucose levels (> 4 per day) with continuous control of dietary regimen and carbohydrate intake, increased physical activity, and the acquisition of skills aimed at self-managing the disease and using technological devices. All these factors have a significant impact on the patient’s life, particularly children and adolescents; young patients with diabetes and their families often experience a significant level of anxiety which impairs their quality of life (QoL) and results in suboptimal diabetes and glucose control [ 13 ]; depressive symptoms in adolescents with T1DM result in poor glycaemic control and are associated with an increased risk of short-term complications [ 14 ].…”
Section: Unmet Needs In the Management Of T1dmmentioning
confidence: 99%
“…The lifetime prevalence of depressive disorders is approximately 6.5-21% [1], and this incidence rate is predicted to become the second leading cause of disability worldwide [2]. Studies have shown that various physical sicknesses and disabilities can induce a depressive phenotype [3][4][5][6]. Among the detected causes, chronic pain is one of the main triggers.…”
Section: Introductionmentioning
confidence: 99%